2012
DOI: 10.3791/3872
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Functional Characterization of Endothelial Colony Forming Cells Derived from Human Umbilical Cord Blood

Abstract: Longstanding views of new blood vessel formation via angiogenesis, vasculogenesis, and arteriogenesis have been recently reviewed 1 . The presence of circulating endothelial progenitor cells (EPCs) were first identified in adult human peripheral blood by Asahara et al. in 1997 2 bringing an infusion of new hypotheses and strategies for vascular regeneration and repair. EPCs are rare but normal components of circulating blood that home to sites of blood vessel formation or vascular remodeling, and facilita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 19 publications
0
34
0
Order By: Relevance
“…Advances in the understanding of how blood cells develop from the hemogenic endothelium helps to interpret the hemato‐endothelial overlap of EPCs . Sophisticated culture protocols have clarified that the PB harbors even smaller populations of endothelial colony forming cells (ECFC), distinct from traditional EPCs . However, whether culture‐defined cell types truly exist in vivo or they represent in vitro artifacts is unknown.…”
Section: Diabetes the Bone Marrow And Circulating Stem/progenitor Cmentioning
confidence: 99%
“…Advances in the understanding of how blood cells develop from the hemogenic endothelium helps to interpret the hemato‐endothelial overlap of EPCs . Sophisticated culture protocols have clarified that the PB harbors even smaller populations of endothelial colony forming cells (ECFC), distinct from traditional EPCs . However, whether culture‐defined cell types truly exist in vivo or they represent in vitro artifacts is unknown.…”
Section: Diabetes the Bone Marrow And Circulating Stem/progenitor Cmentioning
confidence: 99%
“…1). Smooth muscle cells and endothelial cells are exposed to many growth factors and proinflammatory cytokines that contribute to angiogenesis, and p38 MAPK is implicated in downstream cytokine signaling (18,26); therefore, p38 MAPK signaling was analyzed in ECFCs, a subtype of umbilical cord blood-derived endothelial cells that can form intrinsic in vivo vessels upon transplantation into immunodeficient mice (27), and ADSCs, which are similar to mesenchymal stem cells, which can give rise to cells with pericytic properties that can stabilize vascular assembly in vitro (28). In ECFCs, there was a robust increase in VEGF-dependent phosphorylated p38 MAPK (p-p38) expression (p Ͻ 0.05), whereas bFGF, EGF, and IL-6 showed a modest (ϳ25%) increase in p-p38 by a highly sensitive immunoassay (Fig.…”
Section: Vegf Bfgf Egf and Il-6mentioning
confidence: 99%
“…In contrast, studies have shown that EPCs have improved proliferative potential. 10,11 Methods of isolation and largescale expansion of these cells have also been developed. [12][13][14] Early-and late-outgrowth EPCs have been implicated in the repair and function of the endothelium, and the harvest of these cells is less invasive than that of ECs.…”
Section: Introductionmentioning
confidence: 99%